PELATIHAN MENDELEY UNTUK MENGELOLA REFERENSI KARYA TULIS BAGI MAHASISWA UKIP - Sapari, Lili (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
The objectives of Mendeley training for UKiP students are: 1) Train students in creating quotations and bibliography using reference managers; 2) Improve students' writing skills with correct quotations and bibliography; and 3) Improving the quality of student theses. Based on the problems above, the author is interested in providing training to students regarding the use of the Mendeley application in preparing their thesis. The methods used are the planning stage, implementation stage and evaluation stage, adjusted to the facilities the students have. As the purpose of the activity was explained at the beginning. The conclusion of this activity provides the ability to use the Mendeley application as a reference manager in writing a thesis and improves the ability to quote and write a bibliography using a reference manager.